THE TRANSLATING OF ENGLISH IDIOMS INTO INDONESIAN - Priska Meilasari (Universitas Katolik Widya Mandala Surabaya, 2015)
This study discussed English idioms and their renderings. It focused on the strategies used in translating idioms and their renderings fidelity. This research was descriptive in nature. The data were obtained from a novel written by Stephenie Meyer entitled Twilight and the rendering in Indonesian under the same title translated by Lily Devita Sari. The population of this research was all of the sentences containing English idioms within Twilight and the renderings in the Indonesian version of the novel. To get the sample, this research applied total sampling. Therefore, all of the data were analyzed one by one. To judge the strategy used by the translator, translational equivalent method was applied. Likewise, to search the fidelity of the renderings, translational equivalent method was also applied. Based on the strategy used, most idioms in the novel were translated by paraphrase (87 idioms) and only a few idioms were translated by using idioms of the same meaning and dissimilar form (2 idioms). Due to the fidelity of the renderings, most idioms in the novel were translated faithfully by adhering the meaning fidelity (67 idioms). Some other idioms, however, were translated unfaithfully (20 idioms). Key Words : idioms, translation, fidelity.